The Economics of Sustainable Transformation - Szelagowska, Anna; Pluta-Zaremba, Aneta (Taylor & Francis, 2021)
"This book presents the ways in which three key issues of the modern world - transformation, digitalisation and sustainability - may be combined for the greater good and highlights which activities may be designed to integrate these three directly linked paths. It is an experience-derived and evidence-based analysis of how sustainable development impacts the transformation of the economy and how the business environment influences economic transformation in the light of the sustainable development principles. The book addresses the current challenges and shows how the economy can be transformed further in an organic way that meets the needs of society and the environment, through the use of digital technologies. The multidisciplinary approach to sustainability transformation is one of the core strengths of the book, as it emphasises the need for a holistic approach to the functioning of sustainable development ideas at the micro- and macro-levels. The authors present a fresh perspective, particularly around the regulations stimulating the sustainable development of enterprises, tax systems, and the allocation of capital. Moreover, the book brings together and makes available the results of the latest research on the subject, using a vast amount of primary evidence and both quantitative and qualitative methodology. The authors' insights go beyond the obvious effects of economic transformation and call attention to ways in which smart technology and digitalisation may help to achieve the Sustainable Development Goals. The book is directed first and foremost towards academics, researchers and students, but also professionals, who would like to expand their knowledge of sustainable development from a scientific perspective."